The role of libraries in higher education in Africa (2012)
Libraries have been the companions of higher education for many centuries. Library in higher education is supposed to play a critical role in the teaching, research, and learning activities through selection, acquisition, organization, preservation, and given access to all sorts of relevant and current materials which include books and periodicals, manuscripts, rare documents, journals, maps, etc. needed by teachers and students. This paper therefore made an attempt to examine the state of higher education libraries and how they have been able to support the institutions to which they are attached. The academic library is a vital force at the heart of higher education. Yet, its future seems to be uncertain, hence the need to bring into limelight the challenges facing academic library in Africa and offer possible strategies for responding to them. It was discovered that higher education libraries in Africa have not been providing the expected services effectively and efficiently due to the severe economic challenges facing them such as inability to stock libraries with current and relevant information resources, under staffing among others. The study recommended that higher education library should be well funded in order to employ enough staff, acquire materials such as current journals, books, equipment, integrate the use of Information and Communication Technology to carry out their housekeeping operations and services in order to be more effective and efficient in the information delivery, global access to information, and also to easy retrieval of information.